Regulation of lipid‐induced macrophage polarization through modulating peroxisome proliferator‐activated receptor‐gamma activity affects hepatic lipid metabolism via a Toll‐like receptor 4/NF‐κB signaling pathway - Wu, Hui‐Min; Ni, Xi‐Xi; Xu, Qin‐Yu; Wang, Qi; Li, Xiao‐Yun; Hua, Jing (Journal of gastroenterology and hepatology, 2020)
Background and Aim Chronic inflammation links closely to insulin resistance and lipid metabolism in nonalcoholic fatty liver disease (NAFLD). Macrophage M1 activation plays an important role in the initiation and continuing of pro‐inflammatory response of NAFLD. Our study was to investigate whether macrophage M1/M2 polarization switching would affect hepatic inflammation and lipid metabolism through modulation of peroxisome proliferator‐activated receptor‐gamma (PPAR‐γ) activity in vivo and in vitro. Methods RAW264.7 macrophages were treated with different fatty acids, and cell culture supernatants were collected to prepare conditioned media (CM). Different co‐culture systems between primary hepatocytes and CM from macrophages were established. A PPAR‐γ agonist or antagonist was administered to regulate PPAR‐γ activity and macrophage polarization. M1/M2 phenotype markers, inflammatory signaling pathway, and lipid‐related genes expression were determined. Wild‐type C57BL/6 mice were fed a high‐fat diet to induce NAFLD and given rosiglitazone to regulate PPAR‐γ activity in vivo. Results Saturated fatty acids induced M1‐polarized macrophages while polyunsaturated fatty acids induced M2‐polarized macrophages. M1‐polarized macrophages significantly promoted lipid synthesis and accumulation in primary hepatocytes through upregulation of a toll‐like receptor 4 (TLR4)/NF‐κB signaling pathway. The PPAR‐γ agonist made lipid‐induced M1‐polarized macrophages switch to an M2‐predominant phenotype, while PPAR‐γ antagonist had the opposite effect. Macrophage polarization shifting subsequently affected lipid metabolism in primary hepatocytes. Administration of rosiglitazone improved high‐fat diet induced hepatic steatosis and lipid metabolism through reducing hepatic TLR4/NF‐κB expression and M1‐polarized Kupffer cells. Conclusions Lipid‐induced macrophage M1 polarization promoted hepatic lipid metabolism. Modulation of PPAR‐γ activity could shift macrophage polarization and subsequently affect lipid metabolism. Upregulation of the TLR4/NF‐κB signaling pathway is closely linked to dysregulated lipid metabolism in NAFLD.